2018
DOI: 10.1016/j.ecoleng.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from sewage and septage in constructed wetland mesocosms using sand media amended with biochar

Abstract: Biochar has been identified as a media amendment to improve nutrient removal from wastewater, and N retention and plant growth in agroforestry. It therefore has the potential for treating domestic wastewater. The aim of this research was to compare nitrogen removal and plant growth in pure sand and sand amended with biochar, in wetland mesocosms (240 L) receiving sewage. There were seven media treatments based on the proportions of biochar in the sand media (100% sand, sand and coir peat, 5, 10, 15, 20, 25% bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…99 The effect of biochar addition on hydraulic conductivity of biofilter media will depend on the differences in particle size of the biochar and the sand 55,97 and may also depend on the biochar application rate. Addition of biochar to sand media reduced the hydraulic conductivity at higher biochar application rates (>15%), 100 and a ten-fold decrease in hydraulic conductivity compared to sand-only was observed by Ray et al 54 when mixing sand (0.6-0.85 mm) with finer biochar particles (0.1-0.3 mm). On the contrary, biochar application rates of 0.5-2% only led to minimal decreases in hydraulic conductivity of a sandy loam soil.…”
Section: Environmental Science: Water Research and Technology Critical mentioning
confidence: 74%
“…99 The effect of biochar addition on hydraulic conductivity of biofilter media will depend on the differences in particle size of the biochar and the sand 55,97 and may also depend on the biochar application rate. Addition of biochar to sand media reduced the hydraulic conductivity at higher biochar application rates (>15%), 100 and a ten-fold decrease in hydraulic conductivity compared to sand-only was observed by Ray et al 54 when mixing sand (0.6-0.85 mm) with finer biochar particles (0.1-0.3 mm). On the contrary, biochar application rates of 0.5-2% only led to minimal decreases in hydraulic conductivity of a sandy loam soil.…”
Section: Environmental Science: Water Research and Technology Critical mentioning
confidence: 74%
“…Nitrogen influent concentration is one of the factors that affects nitrogen removal processes. Previous studies have shown that the uptake rate of nitrogen was influenced by the inflow concentration; the removal efficiency was more satisfied with the low nitrogen concentration than the high concentration [72,73]. S. Wang [67] observed that the removal efficiency of NO 3 − was low (20.5%) for an influent concentration ranging from 6.15 to 9.61 mg/L.…”
Section: The Effect Of Nitrogen Concentrationmentioning
confidence: 96%
“…The uptake rate usually depends on the plant type and plant growth rate. In fact, good plant growth with higher biomass will result in a better plant uptake and nitrogen removal [72][73][74][75][76], however, rapid plant growth rate also contributes to TN removal [77]. A study by Milandri et al [78] found that the rapid growth rate of the turf grasses, Pennisetum and Stenotaphrum, was effective in NH 3 (97%) and NO 3 − removal (>80%).…”
Section: The Effect Of Vegetationmentioning
confidence: 99%
“…Constructed wetlands (CWs), as an efficient eco‐technology, have been applied extensively in wastewater treatment because of the advantages of their low cost and simple operation and maintenance (de Rozari et al 2018; Nivala et al 2018). Therefore, with the increase in the world population, urbanization, industrialization and the depletion of water resources, CWs have attracted the attention of most countries around the world (Lu et al 2016).…”
Section: Introductionmentioning
confidence: 99%